Applicability of Architectural Design Features in Contemporary Luxury Houses - Mervyn Wong, Hsin Jyi; Joy Natalie, Cotter; Mohd Afzan Noorawavi, Mohamed; Chung, Leng Pau (Springer Singapore, 2024)
This paper investigates the applicability of architectural design features in luxury houses through a case study methodology. This study aims to identify and understand the design principles and aesthetics that influence the design of luxury houses. The case study approach involves the analysis of three luxury contemporary houses in Sarawak, each with unique architectural designs. According to the research, seven elements of designing a luxury house were explained. These include security factors, the volume of space, building materials, façade design, interior design, court- yard, and landscape design. These design aspects are achieved by paying close atten- tion to detail and focusing on creating an atmosphere that promotes the resident’s way of life. The research also emphasizes the significance of implementing sustainable design approaches, which contribute to environmental sustainability and increase the value of luxury home designs. In the context of creating more resilient architecture in the future, passive luxury house design can be an effective way to mitigate the risks of extreme weather conditions. Several passive design strategies were implemented and discussed in this paper to create an energy-efficient, comfortable, and healthy building without relying on active systems such as heating and cooling. This study provides an in-depth analysis of the design elements that are considered essential in luxury house design. The findings of this study can be useful for architects, interior designers, and developers in creating more resilient and sustainable luxury houses that meet the expectations of discerning clients.